Joint association of indoor allergens, endotoxins, heavy metals, and parabens with allergy-related outcomes in U. S. adults - Xue, Min; Wei, Xiaoling; Zhang, Yun; Ma, Xiang (Frontiers in Public Health, 2025)
BackgroundWhile the associations of indoor allergens, endotoxin, heavy metals, and parabens with allergy outcomes are well-studied, the combined association remains unclear. This study examines the association between their combined exposure and allergy outcomes in adults.MethodsA toatl of 1,065 adults from the National Health and Nutrition Examination Survey (NHANES) 2005–2006 were included in analyses. We applied a weighted logistic regression model to investigate the association between individual exposure to 10 chemicals (including Aspergillus fumigatus, Canf 1, Feld 1, Mus m 1, endotoxin, cadmium, lead, total mercury, methyl paraben, and propyl paraben) and allergy-related outcomes. WQS and BKMR models were further used to examine the combined associations.ResultsThe weighted logistic regression model indicated that high-level exposures (Tertile 3 vs. Tertile 1) to Can f 1, Fel d 1, Mus m 1, endotoxin, cadmium, mercury, methyl paraben, and propyl paraben were significantly associated with an increased risk of allergy-related outcomes. In WQS regression analysis, the WQS index was significantly associated with an increased risk of allergy-related outcomes (aOR = 1.49, 95% CI: 1.04–2.11, p = 0.027). Can f 1, methyl paraben, endotoxin and cadmium were the most heavily weighed exposure indicators. In BKMR analysis, overall risk estimates were consistently elevated relative to the 25th percentile reference and increased with higher exposure.ConclusionJoint and individual exposures to multiple environmental pollutants, particularly Can f 1, methyl paraben, endotoxin, and cadmium, are associated with increased allergy risk in adults. These results underscore the need for integrated exposure assessment in allergy prevention strategies.